2006
DOI: 10.1016/j.arr.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction and intermittent fasting: Two potential diets for successful brain aging

Abstract: The vulnerability of the nervous system to advancing age is all too often manifest in neurodegenerative disorders such as Alzheimer's and Parkinson's diseases. In this review article we describe evidence suggesting that two dietary interventions, caloric restriction (CR) and intermittent fasting (IF), can prolong the health-span of the nervous system by impinging upon fundamental metabolic and cellular signaling pathways that regulate life-span. CR and IF affect energy and oxygen radical metabolism, and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(248 citation statements)
references
References 151 publications
5
235
1
7
Order By: Relevance
“…It is possible that the association between increased risk of developing AD and excess body weight reflects the potential effect of a diet high in simple sugars and fats to the development of AD. A recent study showed reducing caloric intake increases healthspan, reduces damage in the brain due to aging, and provides greater maintenance of various brain functions (Martin et al, 2008; Martin, Golden, Egan, Mattson, & Maudsley, 2007; Martin, Ji, Maudsley, & Mattson, 2010; Martin, Mattson, & Maudsley, 2006). …”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…It is possible that the association between increased risk of developing AD and excess body weight reflects the potential effect of a diet high in simple sugars and fats to the development of AD. A recent study showed reducing caloric intake increases healthspan, reduces damage in the brain due to aging, and provides greater maintenance of various brain functions (Martin et al, 2008; Martin, Golden, Egan, Mattson, & Maudsley, 2007; Martin, Ji, Maudsley, & Mattson, 2010; Martin, Mattson, & Maudsley, 2006). …”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…It has been known for many decades that restricting daily calorie intake in rodents and some other animals increases longevity substantially [85,86]. It is speculated that this may be because in times of famine reproductive activity is reduced, since any offspring would be unlikely to survive.…”
Section: Environmental Factors and Brain Ageingmentioning
confidence: 99%
“…In addition to these humoral factors connecting energy balance to reproduction, it has recently been posited that there is a specific glucose-sensing mechanism in the CNS itself that is mediated via noradrenergic stimulation of the nuclei of the solitary tract (NTS: Kinoshita et al, 2003). Profound nutritional signals such as those imposed by CR or IF exert a wide range of physiological effects across the whole organism subjected to the dietary change (for review see Martin et al, 2006). One of the most profound alterations that take place with these dietary regimes is disruption of the complex neuroendocrine feedback axes centered around the anterior pituitary.…”
Section: Dietary Restriction and Reproductive Pituitary Functionmentioning
confidence: 99%
“…In experimental paradigms in various species, it has been shown that specific alterations in available dietary energy, e.g. mild caloric restriction (CR) or intermittent fasting (IF), can have beneficial and long-lasting effects on animal physiology (for review, see Martin et al, 2006). Low, moderate and high levels of dietary energy intake can affect reproductive function in different ways.…”
Section: Introductionmentioning
confidence: 99%